Effect of N and Cu Doping on Structure, Surface Morphology and Photoluminescence Properties of ZnO Thin Films - Liton, M. N.; Khan, K. R.; Rahman, M. M.; Islam, M. M. (Journal of Scientific Research, 2015)
Thin films of ZnO, ZnO:Cu, ZnO:N and ZnO:(Cu,N) have been deposited on glass substrate at temperature 350ºC by low cost spray pyrolysis (SP) technique at an ambient atmosphere. The X-ray diffraction (XRD) study revealed that the films are of mono-phasic polycrystalline in nature having wurtzite ZnO crystal structure. The preferential orientation of un-doped ZnO films is in the (002) plane which changes to (101) for N and Cu mono-doped and (Cu, N) co-doped ZnO films. Surface morphology studied by scanning electron microscopy (SEM) clearly shows the formation of rock shaped nanostructures and hexagonal crystalline grains. The atomic force microscopy (AFM) study revealed the formation of crystalline grains perpendicular to the surface and reduction of surface roughness with doping. The photoluminescence (PL) spectra of the un-doped and doped ZnO samples show well defined transitions of the near band edge (NBE) and deep level (DLE) emissions emerged from different defect states present in the films.